Topical khellin + UVA (KUVA) in the treatment of childhood vitiligo. - Valkova, S.; Trashlieva, M. (European Journal of Pediatric Dermatology, 1999)
The results from the treatment of 10 children with vitiligo (phototype II - III) with topical Khellin + UVA (KUVA) therapy are presented. The irradiation sessions were held in a Waldmann 7001 K cabin and with PUVA 180 and 200 apparatuses. One hour before sessions 5 % khellin in greasy ointment was applied on the vitiliginous lesions. The initial exposure dose depended on phototype and was increased every second procedure. Treatments were given 3 - 4 times weekly. The patients did not receive any additional medicaments except for emollients. As a result of the therapy in all patients different degree of repigmentation (10 - 90 %) was observed. No phototoxic accidents or other side effects were encountered in any of the cases. Because of its low phototoxicity topical KUVA therapy could be used safely during all seasons without risk of developing severe erythema or blistering. It needs a little time and does not necessitate hospitalization of the patients.